Takhrij and Syarah Hadith of Agrotechnology: Farming and The Effects of Land Management - Fitriani Adiningsih; Wahyudin Darmalaksana; Suryaman Birnadi (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research are the main natural sources, namely soil and water that are prone to damage or degradation along with the anticipation to overcome soil damage by carrying out proper land management. The conclusion of this study is that the takhrij and syarah hadiths about farming and land management with agro-technology analysis inform that land management is very beneficial for soil fertility and also affects the yield of farming.